Analysis and design of analog integrated circuits - Gray, Paul R. (John Wiley & Sons, 1997)
This edition combines the consideration of metal-oxide-semiconductors (MOS) and bipolar circuits into a unified treatment that also includes MOS-bipolar connections made possible by BiCMOS technology. Contains extensive use of SPICE, especially as an integral part of many examples in the problem sets as a more accurate check on hand calculations and as a tool to examine complex circuit behavior beyond the scope of hand analysis. Concerned largely with the design of integrated circuits, a considerable amount of material is also included on applications.